ESL Students’ Use of Google Sites in Language Learning through Heutagogy Approach - Ebrahim Panah; Ng Loo Ee; Hafizan Matsom; Nur Atirah Mohd Jalil (Asian TESOL Journal, 2022)
The objective of this study to investigate the use of Google Sites for English language learning. The study used Heutagogy approach (Explore, Create, Collaborate, Connect, Share, and Reflect). A sample of 78 students, who were selected based on purposive sampling, participated in the study. The study adopted a survey approach through using a questionnaire as the instrument to collect data. The obtained data was analysed using SPSS through performing descriptive and correlation analyses. The findings indicate that language learning through website allows students to practice heutagogy approach and as result helping them improve language learning. The findings have implication for students, teachers and education policy makers.